Utilization of Artificial Intelligence in EFL Learning from a Digital Literacy Perspective - Nur Rahmah Wahyuddin; Nur Eva Yanti; Riska Arnas; Sam Hermansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates how university students utilize Artificial Intelligence (AI) in English as a Foreign Language (EFL) learning from a digital literacy perspective. Conducted between February–April 2024, the research involved nine undergraduate students from Universitas Ichsan Sidenreng Rappang who actively used AI tools such as ChatGPT, Grammarly, and Duolingo in their daily learning practices. Using a qualitative thematic analysis, the study explored students’ experiences, challenges, and expectations regarding AI-supported EFL learning. Findings show that AI contributed substantially to improving students’ vocabulary, grammar accuracy, and speaking fluency, with several participants reporting that AI-based feedback helped them understand errors more quickly and increased their learning motivation—some estimating up to a 20–30% improvement in confidence and task completion efficiency. However, issues such as inconsistent responses, fabricated references, and overreliance on AI revealed gaps in students’ critical digital literacy. The study highlights the need for strengthened digital literacy training and more structured integration of AI tools in higher education to ensure ethical, accurate, and effective use of AI for language learning.